'Why can't you just eat pork?' Teachers' perspectives on criticism of religion in Norwegian religious education - Hammer, Aina (Journal of Religious Education, 2018)
Over the last 20 years, religious education in Norway has received massive public and academic attention, due in part to clashing opinions regarding the role of such education in a generally secular society. As a result, the subject's name and curricula have been changed or modified several times. Currently, the curricula for 'Knowledge of Christianity, Religion, Philosophies of Life and Ethics' (abbreviated in Norwegian as KRLE) states the teaching must be critical. This empirical study examines how teachers themselves interpret this requirement. We particularly emphasise the role of criticism of religion, including both the teachers' planned teaching about criticism of religion and the criticism spontaneously uttered by students. The findings demonstrate students' criticism of religion often is of a moral, secular or ridiculing character, and is frequently based on prejudice, stereotypes, generalisations or essentialist notions. This article discusses how teachers can use students' spontaneously uttered criticism of religion as a starting point to develop intercultural competence through education.